Kinerja Pencampuran Pewarna Kunyit dan Indigofera dengan Molaritas Indigo/Kunyit 0,32M/0,23M sebagai Sensitizer Pada Dye Sensitized Solar Cells(DSSCC) - Basuki (Universitas Hasyim Asy'ari, 2018)
The research is to examine the performance of solar cell with turmeric andindigo dye. Turmeric dye is obtained by extraction method while the indigo dye is obtained by fermentation method from indigofera plants. Indigofera and turmeric dyes were treated by mixing dye with indigo / turmeric molarity 0.32M / 0.23M. Characteristics of the dye are studied. The natural dye was tested with absorbance test, FTIR and cyclic voltammetry. The dye mixing was then applied to dye-sensitized solar cells (DSSCs) and then DSSC performance was tested at 0 hours. The UV-Vis results showed that the dye absorption with indigo / turmeric molarity was 0.32M / 0.23M with an absorption peak of 375 -525 nm. From the FTIR test, the dyeing function mixing group with indigo / turmeric molarity of 0.32M / 0.23M is -OH, C = Caromatic, alkane C-H, amina C-N.The result of cyclic voltammetry test showed that mixing dye with indigo / turmeric molarity 0,32M / 0,23M band gap 0,745 eV. Result from this research of solar cellefficiency is 0.038%.